Analisis Determinan Nilai Perusahaan Pada Perusahaan Transportasi di Bursa Efek Indonesia - Maya Sari; Nurul Hariyanti; Ade Gunawan (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
This study aims to determine and analyze the effect of debt to asset ratio, debt to equity ratio, return on assets, return on equity and Asset Growth partially and simultaneously on Firm value. The population used in this study is the population of Transportation companies listed on the Indonesia Stock Exchange, which publishes complete financial statements after being audited starting from the period 2014 to 2017, amounting to 35 companies listed on the Indonesia Stock Exchange. Based on these criteria there are 13 transportation companies that are the author's research samples. The data analysis technique used is multiple linear regression, classic assumption test, t test, F test and coefficient of determination. The research results partially Debt to Asset Ratio has a significant effect on Price Book Value (PBV), Debt to Equity Ratio has a significant effect on Price Book Value (PBV), Return On Asset, partially significant effect on Price Book Value (PBV), Return On Equity, partially significant effect on Price Book Value (PBV), Asset Growth, partially has a significant effect on Price Book Value (PBV) . Simultaneously Debt to Asset Ratio, Debt to Equity Ratio, Return On Asset, Return On Equity, and Asset Growth, simultaneously have a significant effect on Price Book Value (PBV)